2009
DOI: 10.1007/s10563-009-9078-4
|View full text |Cite
|
Sign up to set email alerts
|

Solid Acid Catalysts: Modification of Acid Sites and Effect on Activity and Selectivity Tuning in Various Reactions

Abstract: The effects of acidity and variation in concentration of acid sites of dodecatungstophosphoric acid (DTP), supported DTP and montmorillonite-K catalysts were studied for various organic reactions such as the hydroxyalkylation of phenols to bisphenols, intramolecular rearrangement of benzyl phenyl ether (BPE) to 2-benzyl phenol (2-BP) and selective cleavage of tert-butyldimethylsilyl (TBDMS) ether into the corresponding alcohol. Both dodecatungstophosphoric acid (DTP) impregnated on silica (SiO 2 ) and montmori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 71 publications
1
12
0
Order By: Relevance
“…This is very much coherent with the low temperature acid concentration (1.45%) which is maximum for 60CsTPA-ZTP. Our observation is in agreement with the report published by Rode et al 34 Similar observations were noticed on the formation of BPF with selectivity enhancement from 6.25-87.95% and With further increase in the wt% of CsTPA onto ZTP, the selectivity and rate of formation remain almost same. In case of BPA, biproducts such as chromans and triphenols were not identified, rather a minor quantity of o,p -BPA was observed at higher wt% of CsTPA (>50 wt%) supported ZTP.…”
Section: Characterization Of Catalystssupporting
confidence: 93%
See 2 more Smart Citations
“…This is very much coherent with the low temperature acid concentration (1.45%) which is maximum for 60CsTPA-ZTP. Our observation is in agreement with the report published by Rode et al 34 Similar observations were noticed on the formation of BPF with selectivity enhancement from 6.25-87.95% and With further increase in the wt% of CsTPA onto ZTP, the selectivity and rate of formation remain almost same. In case of BPA, biproducts such as chromans and triphenols were not identified, rather a minor quantity of o,p -BPA was observed at higher wt% of CsTPA (>50 wt%) supported ZTP.…”
Section: Characterization Of Catalystssupporting
confidence: 93%
“…As observed, the pristine ZTP 17 having highest surface area, i.e., 102 m 2 /g shows the lowest phenol conversion, i.e., 3% and 6.5%, lowest selectivity, i.e., 5% and 6.25% towards the formation of BPA and BPF, respectively. This is because of the fact that ZTP contains strong acidic sites at high temperature (HT), 33,34 which are not effective for the formation of p,p -BPA. Also, CsTPA shows the conversion, i.e., 10% towards BPA and BPF with 5% selectivity for BPA and 7.2% BPF.…”
Section: Characterization Of Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exchangeable cations between the mont layers can be readily replaced under mild conditions in various precursor solutions. For example, proton-exchanged mont (H-mont) is easily ion-exchanged by heating and stirring Na-mont at 90 °C in HCl aqueous solution (figure 2) [17]. For Al-mont, representative conditions are at 50 °C in AlCl 3 aqueous solution.…”
Section: Catalysis Of Cation-exchanged Montmorillonitementioning
confidence: 99%
“…The glycerol etherification with isobutene using sulfonic acid functionalized solid acid showed the highest conversion of glycerol with high selectivity to di-and tri-glycerol ethers (79-91%) in comparison to non-sulfonated solid acid catalysts, which suggested that high activity and selectivity for etherification of glycerol can be achieved over catalysts with high acid strength and appropriate pore structure (Gonzalez et al 2013;Wilson and Clark, 2000;Garade et al 2010a). Hence, solid acids such as heteropoly acids (HPAs) supported catalysts could be a suitable option for etherification of glycerol due to higher Bronsted acid, recyclability, and stability (Sepulveda et al 2011;Rode et al 2009;Garade et al 2010a;Roze et al 2013;Liu et al 2013b;Magar et al 2017). The present studies have enhanced the economy of biodiesel production via conversion of by-product glycerol into oxygenated fuel additives.…”
Section: Introductionmentioning
confidence: 99%